CRISPR/Cas13a-Assisted accurate and portable hepatitis D virus RNA detection - Yuan Tian; Zihao Fan; Xiangying Zhang; Ling Xu; Yaling Cao; Zhenzhen Pan; Yinkang Mo; Yao Gao; Sujun Zheng; Jing Huang; Huaibin Zou; Zhongping Duan; et al. (Emerging Microbes and Infections, 2023)
Background & Aims Hepatitis delta virus (HDV) infection accelerates the progression of chronic hepatitis B virus (HBV) infection, posing a large economic and health burden to patients. At present, there remains a lack of accurate and portable detection methods for HDV RNA. Here, we aim to establish a convenient, rapid, highly sensitive and specific method to detect HDV RNA using CRISPR–Cas13a technology.Methods We established fluorescence (F) and lateral flow strip (L) assays based on CRISPR–Cas13a combined with RT–PCR and RT-RAA for HDV RNA detection, respectively. we conducted a cohort study of 144 patients with HDV-IgG positive to evaluate the CRISPR–Cas13a diagnostic performance for identifying HDV in clinical samples, compared to RT–qPCR and RT-ddPCR.Results For synthetic HDV RNA plasmids, the sensitivity of RT–PCR-CRISPR-based fluorescence assays was 1 copy/μL, higher than that of RT–qPCR (10 copies/μL) and RT-ddPCR (10 copies/μL); for HDV RNA-positive samples, the sensitivity of RT-RAA-CRISPR-based fluorescence and lateral flow strip assays was 10 copies/μL, as low as that of RT–qPCR and RT-ddPCR, and the assay took only approximately 85 min. Additionally, the positivity rates of anti-HDV IgG-positive samples detected by the RT–qPCR, RT-ddPCR, RT–PCR-CRISPR fluorescence and RT-RAA-CRISPR lateral flow strip methods were 66.7% (96/144), 76.4% (110/144), 81.9% (118/144), and 72.2% (104/144), respectively.Conclusions We developed a highly sensitive and specific, as well as a portable and easy CRISPR-based assay for the detection of HDV RNA, which could be a prospective measure for monitoring the development of HDV infection and evaluating the therapeutic effect.